2015
DOI: 10.1111/sms.12631
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and tendon adaptation in adolescent athletes: A longitudinal study

Abstract: There is evidence that a non-uniform adaptation of muscle and tendon in young athletes results in increased tendon stress during mid-adolescence. The present longitudinal study investigated the development of the morphological and mechanical properties of muscle and tendon of volleyball athletes in a time period of 2 years from mid-adolescence to late adolescence. Eighteen elite volleyball athletes participated in magnetic resonance imaging and ultrasound-dynamometry sessions to determine quadriceps femoris mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 41 publications
2
43
0
1
Order By: Relevance
“…9 Mersmann et al demonstrated that while transitioning from early to late adolescence, the patellar tendon CSA and stiffness increased, as did tendon strength. 10,11 This evidence supports the hypothesis that adolescence is a critical time for tendon development.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…9 Mersmann et al demonstrated that while transitioning from early to late adolescence, the patellar tendon CSA and stiffness increased, as did tendon strength. 10,11 This evidence supports the hypothesis that adolescence is a critical time for tendon development.…”
Section: Introductionsupporting
confidence: 83%
“…Considering that PHV measures the accelerated growth in long bones of the lower limb, it is consistent that after this growth spurt, the patellar tendon would thicken. The findings in this longitudinal study are consistent with a previous cross‐sectional study and a longitudinal study that found patellar tendon hypertrophy was associated with late adolescence; however, it is inconsistent with another study, which found no change in patellar tendon thickness in asymptomatic tendons over adolescence although participants were already 15‐16 years of age at the start of that study. Increasing tendon thickness may be an adaptive mechanism to cope with the sudden increase in femur length and muscle mass that increases tensile loading on the tendon.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Earlier work of our group already provided evidence that under the influence of maturation and superimposed mechanical loading the development of muscle morphology and function might precede adaptive and developmental processes at the tendon level in adolescent volleyball athletes (Mersmann et al, 2014, 2017). The results of a recent meta-analysis indicate an increase in the responsiveness of the neuromuscular system to mechanical loading early in adolescence (Moran et al, 2016), which is likely in part related to the muscle-anabolic effects of sex hormones (Vingren et al, 2010; Hansen and Kjaer, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…More recently, a cross-sectional comparison of tendon thickness between 500 adolescent athletes from different sports provided an indication of tendon plasticity in response to increased loading for the patellar tendon as well (Cassel et al, 2016). Earlier work of our group already suggested that the patellar tendon is responsive to mechanical stimulation, but it was not possible to differentiate the effects of mechanical loading and maturation (Mersmann et al, 2017) or to directly compare the mechanical properties of the patellar tendon between athletes and controls due to inhomogeneous sample composition with regard to sex (Mersmann et al, 2016). The different normalized patellar tendon stiffness between athletes and controls in the present study provide evidence that also the patellar tendon adapts to mechanical loading before adulthood.…”
Section: Discussionmentioning
confidence: 99%